Safe space? - Lé Kay, Caryn Britney (Rhodes University, 2026)
This mini-thesis explores the relationship between ‘safe space,’ female fear, and the potential for violence through a practice-led investigation centered on visual trace-making and storytelling. Working primarily with porcelain as a main material metaphor, my practice transforms overlooked architectural elements, specifically floor tiles and brick pavers, into delicate, breakable porcelain artworks. My intentional use of porcelain emphasises the tension between structural durability and symbolic fragility. The written component supports my practical exploration, drawing upon the work of Pumla Dineo Gqola ‘s Female Fear Factory (2021), to unpack the mechanisms that sustain female fear within a context of gender-based violence in South Africa; also referencing Tim Cresswell’s, Place: a short introduction (2004), to unpack the fundamental components of human geography, and highlight familiar everyday uses of the term ‘place’ in relation to the term space. Finally, by integrating the literature of Ralph Rugoff’s Scene Of The Crime (1997), I explore forensic aesthetics and observe how violence leaves both visible and invisible traces behind; as a sculpture student, I extend this inquiry by deliberately materialising traces through mould-making and slip casting, thereby giving tangible form to the concept of presence and absence. Through engagement, both my mini-thesis and practice-led research facilitates a dialogue around gendered violence, reflecting how any space holds the potential for violence, be it public or private.
a visual dialogue through the art of trace-making and storytelling
Keywords: Women--Violence against—South Africa (http://id.loc.gov/authorities/subjects/sh2022007441); Fear of crime (http://id.loc.gov/authorities/subjects/sh87002889); Pottery molds (http://id.loc.gov/authorities/subjects/sh2001008207); Porcelain in art (http://id.loc.gov/authorities/subjects/sh2006003965); Gender-based violence in art (http://id.loc.gov/authorities/subjects/sh2024001361); Fine Art